Produkcji biowodoru z odpadów w warunkach fermentacji = Hydrogen production condition from waste by dark fermentation - Suchowska-Kisielewicz, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Currently, there is a noticeable dynamic increase in the use of hydrogen in the world amounting around 12% per year. It is expected that by 2025 it will increase by about 8-10%. Currently used methods of hydrogen production are very energy intensive. The article presents the current state of knowledge regarding the effectiveness, challenges and perspectives of hydrogen production from waste in conditions of dark fermentation.
Keywords: biowodór; wstępne przetwarzanie odpadów; fermentacja; biohydrogen; pre-treatment of waste; fermentation